Increase in Local Own Revenue for Maros Regency Sourced from Parking Fees at Unwaved Beaches - Ady Hermawansyah; Muhammad Ihsan Syarif (Universitas Negeri Makassar, 2022)
In the era of regional autonomy, each region is given the authority to optimize its potential which then becomes local revenue. Maros Regency has the potential for local revenue sourced from parking fees in the Unwaved Beach Culinary Area (PTB). The revenue obtained from the Roadside Parking Retribution in the Unwaved Beach Culinary Area (PTB) received by the Maros Regency government is still far from the government's target even though this is one of the sources of Regional Original Revenue (PAD) in Maros Regency. Based on these problems, this study aims to see how effective parking management is in the PTB culinary area and to see whether parking fees in the PTB culinary area can have a positive effect on the income of Maros Regency. The research method used is a mixed method consisting of qualitative and quantitative data collection techniques, namely observation, interviews, and documentation. The research results obtained from the research conducted are that the collection of fees in the Culinary Area of the Unwaved Beach is considered to have the potential to increase Local Own Revenue. From the research conducted, it is found that there are several problems related to efforts to increase local revenue sourced from parking fees, including the absence of regulations governing the collection of parking fees in the Culinary Area of the Unwaved Beach and limited parking space. From these problems, there are recommendations as an alternative solution, namely updating Regional Regulation Number 17 of 2011 concerning Public Service Retribution and making a Regent Regulation for the Culinary Area of the Unwaved Beach